2014
DOI: 10.1016/j.pan.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic spleen-preserving distal pancreatectomy with and without splenic vessel preservation: The role of the Warshaw procedure

Abstract: Background/Objectives: Laparoscopic spleen-preserving distal pancreatectomy (LSPDP) for low-grade

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
4
23
0
1
Order By: Relevance
“…All splenic infarctions occurred after a Warshaw procedure as previously reported by others [36][37][38] . In contrast, clinically relevant splenic infarctions were not observed after the Kimura technique in the presented collective.…”
Section: Discussionsupporting
confidence: 52%
“…All splenic infarctions occurred after a Warshaw procedure as previously reported by others [36][37][38] . In contrast, clinically relevant splenic infarctions were not observed after the Kimura technique in the presented collective.…”
Section: Discussionsupporting
confidence: 52%
“…The search strategy yielded 411 articles and we checked the title and abstract of the studies according to the inclusion and exclusion criteria and selected 53 articles. After the full texts of the remaining articles were read, 15 articles were included in the meta-analysis of MI-SPDP versus MI-DPS [13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 15 articles were included in the meta-analysis of MI-SVP versus MI-WT [13,23,[31][32][33][34][35][36][37][38][39][40][41][42][43]. Figure 1 shows the flow diagram of study identification and evaluation during the review process.…”
Section: Resultsmentioning
confidence: 99%
“…Splenic vessels are resected and the spleen survives via the short gastric and left gastroepiploic vessels (16). Matsushima et al reported on the operative outcomes of 17 cases that underwent Lap-W. Splenic infarctions were observed in four patients (24%) and perigastric varices were observed in two patients (12%) (22). All these patients were observed conservatively.…”
Section: Discussionmentioning
confidence: 99%
“…All these patients were observed conservatively. Matsushima described the importance of preserving not only the short gastric vessels but also the splenocolic ligament and left gastroepiploic vessels in order to retain the blood supply to the spleen in the Warshaw operation (23), and considered that the laparoscopic method of the Warshaw operation may be a more feasible way to preserve the blood supply to the spleen, since a laparoscopic technique can visualize thinner vessels and can therefore avoid unnecessary vessel treatment (22).…”
Section: Discussionmentioning
confidence: 99%